ANALISIS URGENSI PRINSIP 5C (CHARACTER, CAPACITY, CAPITAL, COLLATERAL, CONDITION) DALAM MEMINIMALISIR RISIKO PEMBIAYAAN (STUDI PADA BMT AS’ADIYAH SENGKANG) - Jumarni Jumarni; Lilis Sariani (Fakultas Ekonomi dan Bisnis Islam IAIN Bone, 2021)
ABSTRACTThe implementation of the 5C principles in financial institutions is often not carried out optimally, one of the contributing factors is the existence of targets that must be achieved and the urgent needs of customers so that they take various ways so that their financing applications are accepted. So in this case the author conducted research on the analysis of the urgency of the 5C principle (character, capacity, capital, collateral, condition) in minimizing financing risk. The type of research used is field research using a qualitative approach, where the data collected is in the form of data from interviews, observations, and documentation. And the data analysis technique used is descriptive data analysis.The results of this study indicate that the 5C principle is very important in assessing the financing feasibility of a prospective customer because the 5C principle has an impact on the success of a financing. The implementation of the 5C principles has been carried out well but risks still exist, both risks originating from customers and unexpected risks. Keywords: 5C principle, financing risk.